MICROBIOLOGICAL QUALITY OF THE WATER CONSUMED BY ANIMALS IN A RURAL AREA OF ILHA SOLTEIRA, SÃO PAULO - Fialho, J. M.; Leite, M. A.; Pião, A. C. S.; Dornfeld, C. B.; Do Prado, H. F. A. (Revista Brasileira de Engenharia de Biossistemas, 2016)
Because rural producers have little information about the importance of the water quality, in general, it is difficult to know the characteristics of the water supplied to the animals, making them susceptible to waterborne diseases and posing a threat to public health by exposing the population that consumes their products to the risks of contracting diseases. To this end, the water supplied to dairy herds of eighteen rural lots of Ilha Solteira was evaluated for coliform bacteria, turbidity, pH and electrical conductivity between January and September 2015. The obtained data were compared with the requirements established by CONAMA Resolutions nº 357/2005 and No 396/2008. Although total coliforms were not among the legislation parameters for this purpose, they were detected in all lots, 83% of which presented thermotolerant coliforms, with results ranging from <3.0 to 210 MPN/100 mL and 93% were positive for Escherichia coli. The analysis results showed that 6% of the lots had microbiological parameters that did not fulfill the legislation requirements and in 11%, the pH was below standard required by the legislation.